Mozart’s Sonata for Two Pianos K448 in D-Major 2nd Movement terhadap Memori Jangka Pendek pada Mahasiswa - Nai, Ayu Muhriyani; Renjaan, Aphroditha Salsabilla; Natsir, Anisa Muthmainnah; Alwi, M. Ahkam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Classical music by Mozart is known to stimulate brain waves that support the enhancement of short-term memory. This study aims to examine the effectiveness of listening to Mozart’s classical music in improving short-term memory in university students. This research employed an experimental method with a randomized pretest-posttest control group design. Using purposive sampling, the study involved 20 students from Universitas Negeri Makassar. Participants were divided into two groups: 10 students in the experimental group who listened to Mozart’s classical music while performing a task involving memorizing nonsense syllables, and 10 students in the control group who completed the same task without music. The results showed that the average short-term memory score in the experimental group increased from 9.10 in the pretest to 12.20 in the posttest, with an average gain of 3.10. In the control group, the average score increased from 8.90 to 10.00, with a gain of 1.10. An independent samples t-test indicated a significant difference in posttest scores between the experimental and control groups, with a p-value of 0.007 (p 0.05).